The Effect of Bore Loi on the Comfort of the Body in the Concept of Pine Lining in the Bima Community - ., Sukmawati; ., Aniharyati; Widarti, Luluk (KnE Life Sciences, 2019)
Bore Loi is a kind of herb known to the people of Bima, and is a heritage from ancient times. Bore Loi is an herb that is made as a ”scrub” which is applied (bore) to the entire body, and let it dry for 16 hours and cleaned the next day with a warm bath. The purpose of this study was to determine the effect of Bore loi (Spice Body Scrub) on the comfort of the freshness of the body of the Bima community in Bolo Village RT 11 RW 03 Madapangga District Bima, this study used the ”One Group Pretest-Posttest Design” method, the researchers tested the changes occurred after an experiment or an intervention. In this study a Wilcoxon test statistic test with a significance level of p ≤ 0.05 was used. Observation 1 respondent as many as 39 people stated uncomfortable after the bore loi action, the second observation experienced a change in which of the 39 respondents 28 people still felt uncomfortable and 11 people felt comfortable. Then a third observation was taken for 28 respondents and the results obtained where of the 28 respondents who did the re-observation there were 24 people felt comfortable and 4 people still felt uncomfortable, this was due to several factors such as age, and physical activity. Wilcoxon Test statistical test results, where from the test results obtained P value = 0.000 <0.05 with a confidence level of 95%. This means that Ho is rejected and H1 is accepted by the influence of bore loi (LulurRempah).